2018
DOI: 10.1016/j.fertnstert.2018.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Ninety babies born after round spermatid injection into oocytes: survey of their development from fertilization to 2 years of age

Abstract: UMIN Clinical Trials Registry UMIN000006117.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 21 publications
(24 reference statements)
0
55
0
Order By: Relevance
“…A piece of testicular tissue was taken for only histopathologic examination to evaluate stages of spermatogenesis in the absence of mature spermatozoa on mTESE. This information could give as opportunity for future treatment options such as round spermatid injection (ROSI) into oocytes in the presence of late maturation arrest 23 . Additional GCNIS was not examined with the specific immunohistochemical markers.…”
Section: Discussionmentioning
confidence: 99%
“…A piece of testicular tissue was taken for only histopathologic examination to evaluate stages of spermatogenesis in the absence of mature spermatozoa on mTESE. This information could give as opportunity for future treatment options such as round spermatid injection (ROSI) into oocytes in the presence of late maturation arrest 23 . Additional GCNIS was not examined with the specific immunohistochemical markers.…”
Section: Discussionmentioning
confidence: 99%
“…The microinsemination technique was primarily developed by Yanagimachi and colleagues in 1995 using mice 39 . This technique has already been employed to assist human reproduction, and no overt abnormalities have been reported to date 16,17 . A combined technique including testis piece transplantation, RA treatment, and microinsemination might be practical to restore spermatogenesis, especially in prepubertal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on the postnatal development of 108 babies born after fertilization of oocytes by round spermatid injection (ROSI), 90 of them in Japan and 18 in Spain [59], did not show any significant differences as compared with naturally conceived babies in either physical or cognitive development during the first 2 years after birth, and none of them developed any of the syndromes associated with genomic imprinting defects [59]. Thus, the use of immature male germ cells for fertilization, in spite of the still relatively low success rates, does not appear to be associated with an increased risk of epigenetic abnormalities in the offspring.…”
Section: Fertilization With Immature Male Germ Cellsmentioning
confidence: 99%
“…As to fertilization by ICSI with immature (testicular) spermatozoa and by round spermatid injection (ROSI), the initial fears that incomplete or defective DNA methylation and chromatin configuration of these immature germ cells might cause syndromes related to genomic imprinting abnormalities [90] were not confirmed. In fact, no increase in the frequency of health problems caused by genomic imprinting abnormalities, such as Beckwith-Wiedemann, Prader-Willi, and Angelman syndromes, has been detected in children born after ICSI with testicular spermatozoa [91] and ROSI [59]. A recent study [92] has suggested that the supposed increase of imprinting errors, present in the sperm of infertile patients, does not have an obvious influence on assisted reproduction outcome or the imprinting of offspring, probably because the imprinting errors in sperm are selectively discarded or corrected during development [20,93].…”
Section: Current Clinical Experiencementioning
confidence: 99%